HUBUNGAN KESELAMATAN DAN KESEHATAN KERJA (K3) DENGAN KINERJA KARYAWAN PADA PT. UOB INDONESIA CABANG BENGKULU - Ida Ayu Er. Meytha Gayatri (UNIVED Press, 2015)
Ida Ayu Er. Meytha Gayatri; The purpose of this study was to determine the relationship of Occupational Health and Safety (K3) place. the performance of employees in the branch of PT. UOB Indonesia Bengkulu Branch. From the calculation of the Spearman rank correlation coefficient analysis of the amount of 0.89 or 0.80 to 1.000 rho in a very strong, which means that the relationship between the variables of Occupational Health and Safety (K3) with the performance of employees of PT. UOB Indonesia Bengkulu Branch relate very strong. Hypothesis testing results, from 14.863 t and t table is 2.0003 or (14.863> 2.0003), then Ho is rejected and Ha accepted means there is a significant relationship between occupational safety and health (K3) with the performance of employees at PT. Branch UOB Indonesia Bengkulu branch.Key Word: Health and Safety(K3), Officer Performance